PENGARUH STRUKTUR KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PT ULTRAJAYA MILK INDUSTRY Tbk PERIODE 2009-2023 - Ananda Dwita Safatila; Nurismalatri Nurismalatri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of ownership structure and company size on financial performance at PT. Ultrajaya Milk Industry 2009-2023. The research method used is quantitative. The data source for this research is secondary data in the form of the Annual Report, the annual financial report published for the 2009-2023 period. The analytical methods used are descriptive statistical analysis tests, classical assumption tests, multiple linear regression, t tests and F tests, as well as the coefficient of determination. The results of this research indicate that partially Managerial Ownership has no effect on financial performance with a t- statistic value of 1.047339 which is smaller than the t table (-1.047339<1.796) with a Prob value. Amounting to 0.3174 is greater than 0.05 (0.3174>0.05), Institutional Ownership has no partial effect on financial performance with a t-statistic value of 1.346476 which is smaller than the t table (1.346476<1.796) with a Prob value. 0.2052 is greater than 0.05 (0.2052>0.05), and partially company size has a significant positive effect on financial performance with a t-statistic value of 3.733802 which is greater than the t table (3.733802>1.796) with a Prob value. 0.0033 is smaller than 0.05 (0.0033<0.05). Simultaneously Managerial Ownership, Institutional Ownership and Company Size have a significant positive effect on PT's Financial Performance. Ultrajaya Milk Industry. with a calculated F value of 5.752613 which is greater than Ftable (5.752613>3.587) with a Prob value. amounting to 0.012879. Less than 0.05 (0.012879<0.05). Determination of R Square (R²) is 0.504562. So (KD = r² x 100% = 0.50 x 100% = 50%) it can be concluded that the contribution of the variables Managerial Ownership, Institutional Ownership and Company Size simultaneously influence Financial Performance by 50% while the remaining 50% is influenced by other factors outside this regression equation or variables not examined in this study.